Pengaruh Tingkat Kemasakan Buah, Metode Ekstraksi Buah, Metode Pengeringan, Jenis Kemasan, dan Lama Penyimpanan pada Mutu Benih Jarak Pagar (Jatropha curcas) - Memen Surahman; Endang Murniati; Fifin Nashirotun Nisya (Jurnal Ilmu Pertanian Indonesia, 2013)
Provision of jatropha (Jatropha curcas) seeds along with providing high yielding varieties, is needed to ensure high seed quality. This experiment aimed to observe the pattern of jatropha seed treatment, namely the effect of fruit maturity, fruit extraction methods, seed drying, seed packaging type, and storage duration of seed on the seeds quality. The experiment was conducted from June to November 2011. Jatropha plants used as sources of seeds were obtained from jatropha plantations PT Indocement Tunggal, Tbk, Citeureup, Bogor. Seed handling experiments was conducted at the Seed Technology Laboratory, IPB. The results showed that the level of fruit maturity did not significantly affect the moisture content of seeds, the seeds germination and speed of seedlings growth, but it was significantly affect the dry weight of seed, dry weight of normal seedling, and oil content. The fruit extraction affected the time of peeling, duration of seed sortage, amount of impurities and the extent of seed damage, but it was not significantly affect the seed germination. The seed drying did not significantly affect the seed germination. The length of storage that can retain up to 51% seed germination during 3 months storage was the seed that have been stored in earthen barrel.